1996
DOI: 10.1055/s-2007-1012038
|View full text |Cite
|
Sign up to set email alerts
|

Heart Transplantation in Patients With Diabetic End-Organ Damage Before Transplantation

Abstract: Diabetes mellitus with preexisting end-organ damage (EOD) is considered a contraindication for heart transplantation. The outcome of such patients has not been well characterized. Among 138 patients transplanted between 12/88 and 7/94, 29 were diabetic (11 insulin-dependent); of these, 12 had preexisting EOD, defined as a creatinine clearance < or = 50 ml/min, a 24-hour urine protein concentration > or = 500 mg/L or typical symptoms of peripheral or autonomic polyneuropathy, and 17 had no EOD. We compared diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…19 In the current study, the incidence rates of acute rejection and CMV infection were not different from those of non-diabetics, in line with previous studies. 4,5,8,9,11 An impaired oral glucose tolerance before heart transplantation was recently described as a suitable predictor of the development of post-transplant diabetes. 13 Thus, post-transplant diabetes is most likely steroid-induced in patients with pre-existing glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 In the current study, the incidence rates of acute rejection and CMV infection were not different from those of non-diabetics, in line with previous studies. 4,5,8,9,11 An impaired oral glucose tolerance before heart transplantation was recently described as a suitable predictor of the development of post-transplant diabetes. 13 Thus, post-transplant diabetes is most likely steroid-induced in patients with pre-existing glucose intolerance.…”
Section: Discussionmentioning
confidence: 99%
“…7 These data have encouraged an extension of heart transplant candidates comprising diabetics with end-organ damage in some institutions, with apparently no disadvantageous outcome. 8,9 In the recent literature, however, one study found an increased risk of serious infection 10 and another noted decreased long-term survival. 11 These results were supported by findings from a large multi-center cardiac transplant research database wherein diabetes mellitus was an independent predictor of death in the late posttransplant phase.…”
mentioning
confidence: 99%
“…Although experience with insulin-treated DM in HT recipients is limited (Badellino et al, 1990;Ladowski et al, 1990;Munoz et al, 1992;Faglia et al, 1990;Livi et al, 1994a) even patients with end-organ damage prior to transplantation do not show a difference in mortality rate and complications (i.e. ; rejection episodes, major and minor infections and graft atherosclerosis) compared to the controls (Aleksic et al, 1996). Two of the retrospectively performed analyses from different centers did not show an increase in risk of rejection, infection, renal dysfunction or CAD in a mixed group (insulin-treated, non-insulin-treated) of diabetic patients (Ladowski et al, 1990;Munoz et al, 1992;Livi et al, 1994b).…”
Section: Introductionmentioning
confidence: 99%
“…Although some of these studies have shown that DM patients had a higher incidence of infections and a stronger progressing of graft vascular disease, 1‐ to 4‐year survival did not differ significantly compared with non‐DM patients [12,13]. In 1996, Aleksic et al [14] reported that heart transplant recipients with advanced DM had a similar 1‐year survival rate compared with non‐DM patients, despite of slightly higher CMV infections in the group with DM. Others also found no differences in morbidity and mortality between groups with no DM, moderate DM, and advanced DM [15].…”
Section: Discussionmentioning
confidence: 99%